Language-in-education policy issues and Karl Marx’s views on education - Mokibelo, Eureka (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper examines Botswana Language-in-Education Policy (LiEP) by relating it to the role of education as perceived by Karl Marx’s philosophy on ethnic minority groups in primary schools in Botswana. Botswana LiEP still recognizes only two languages of instruction despite the fact that it is a multilingual society with an estimation of 28 languages spoken in the country. The Marxist perspective on education is used as bedrock to describe the relevance of some of its principles and what the policy prescribes in primary school classes through citing some researches. All the cited researches were investigated through a qualitative approach using a questionnaire with open ended questions, interview, class observations, focus groups and field notes. The findings of these studies reveal that there are: inequalities in Primary School classes and beyond, lack of progression to the next levels of education, communication barriers which present themselves in many faces, and poor hostel conditions that impede on learners completion of lower education. This paper has concluded that indeed the capitalist education system imposes its ideology through the LiEP and it presents inequalities amongst learners in classrooms and beyond.